2020
DOI: 10.1121/10.0000582
|View full text |Cite
|
Sign up to set email alerts
|

Variability in the rigid pinna motions of hipposiderid bats and their impact on sensory information encoding

Abstract: Many bat species, e.g., in the rhinolophid and hipposiderid families, have dynamic biosonar systems with highly mobile pinnae. Pinna motion patterns have been shown to fall into two distinct categories: rigid rotations and non-rigid motions (i.e., deformations). In the present work, two questions regarding the rigid rotations have been investigated: (i) what is the nature of the variability (e.g., discrete subgroups or continuous variation) within the rigid motions, (ii) what is its acoustic impact? To investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 57 publications
2
4
0
Order By: Relevance
“…Rhinolophidae and Hipposideridae families synchronize the movement of their left and right pinnae with pulse emission [19][20][21][22]. This active listening behavior has been reported for constant frequency-frequency modulated (CF-FM) bats, who use a compound signal consisting of a CF part and an FM part (Fig 1A).…”
Section: Introductionsupporting
confidence: 60%
“…Rhinolophidae and Hipposideridae families synchronize the movement of their left and right pinnae with pulse emission [19][20][21][22]. This active listening behavior has been reported for constant frequency-frequency modulated (CF-FM) bats, who use a compound signal consisting of a CF part and an FM part (Fig 1A).…”
Section: Introductionsupporting
confidence: 60%
“…Several species of bats employ behavioral solutions for echo source direction detection. The Rhinolophidae and Hipposideridae families synchronize the movement of their left and right pinnae with the pulse emissions [19][20][21][22]. This active listening behavior has been reported for constant frequency-frequency modulated (CF-FM) bats, who use a compound signal consisting of a CF part and an FM part (Fig 1A).…”
Section: Introductionsupporting
confidence: 57%
“…to alternate between rigid and non rigid motions [107] and have been shown to possess a large range of variability at least in the rigid motions [108]. Hence, it may be hypothesized that this variability provides a substrate for adaptation that would allow the animals to encode more useful sensory information.…”
Section: Discussionmentioning
confidence: 99%
“…The biomimetic sonarhead in our experiment used the same simplified pinna and noseleaf motions for the entire dataset, however bats are known to be capable of different types of movements, classified as rigid and non rigid [107]. It has also been shown that the rigid motions show a large range of variability in the rigid motions [108]. Therefore the potential exists for different motions to be adapted to specific tasks which could enable greater information encoding within foliage echoes.…”
Section: Discussion Of Findingsmentioning
confidence: 99%